Kepemimpinan Dalam Studi Al Qur’an Dan Hadits - Rivaldi Rivaldi; Kasim Yahiji; Misbahuddin Misbahuddin (Departement of Mathematics Education, 2024)
Leadership is a form of scientific and artistic study, which explains how to become a leader who can be a good example for others. Leadership is the ability that a person has in creating a comfortable environment and being able to influence a group or other people in achieving the desired goals. In the process of influencing, this is done by arranging sentences and words, then providing exemplary examples for those they lead through advice on policies that have been agreed upon jointly.In order for an organization to be successful and achieve the goals set based on the Al- Qur'an and Hadith, leaders have a big responsibility. A leader has great authority in running a company. This includes supervision, operation, regulation and institutional structuring. The personality of a leader is compared to the face of an organization. In the view of society, especially the individuals they lead, the organization will also have a positive reputation if its leaders excel. Therefore, in this situation it is very important for a leader to understand and master the ideas, components and characteristics of leadership from a leadership perspective. Therefore, the aim of this article is to provide a clearer explanation regarding the meaning, theory, components, characteristics and application of leadership attitudes in terms of the Al-Qur'an and Hadith. Research from libraries and literature reviews were used in this research. Because the information or sources used to compile this article—such as books, journals, and other materials—come from libraries, it is called library research.